Preparation and filling of small oval root canals: influence of file system and sealer. - Eichelsdoerfer, Katharina; Buettner, Katharina; Lohbauer, Ulrich; Petschelt, Anselm; Metzger, Zvi; Ebert, Johannes (Quintessence International, 2022)
OBJECTIVE: To carry out a morphometric analysis of small oval root canals prepared with different instruments (part 1) and filled with different sealers (part 2). METHOD AND MATERIALS: Ninety extracted mandibular incisors with small oval root canals were instrumented with Self-Adjusting File (n = 45), XP-endo Finisher (n = 15), GentleFile (n = 15), or Reciproc (n = 15). All groups of part 1 were filled with AH Plus (n = 15 each). For part 2 (including group Self-Adjusting File/AH Plus) teeth instrumented with Self-Adjusting File were additionally filled with GuttaFlow Bioseal (n = 15) or Total Fill BC sealer (n = 15). All sealers were placed with a lentulo and filled with master point and additional points. Serial cuts were made at 1-mm intervals up to 10 mm. Total root canal area, percentage of gutta-percha filled area (PGFA), sealer, voids, and debris were evaluated using interactive image analysis software. RESULTS: Preparation with Reciproc caused significantly wider canals than with Self-Adjusting File, GentleFile, or XP-endo Finisher, but also resulted in the greatest PGFA and lowest percentage of sealer (P ≤ .05). Following XP-endo Finisher, the significantly greatest percentage of debris (30%) was found 1 mm from the apex (P ≤ .05). Regarding different sealers, only minor differences were found (GuttaFlow Bioseal: less percentage of sealer at 2 and 3 mm levels [P ≤ .05]). CONCLUSION: Within the limits of this study Reciproc caused the greatest substance loss, but also the most favorable PGFA. The apical debris accumulation with XP-endo Finisher needs further investigation. The sealers under investigation performed equally well.
EVALuna2:512599